2019
DOI: 10.1097/md.0000000000014160
|View full text |Cite
|
Sign up to set email alerts
|

Acupotomy for the treatment of lumbar spinal stenosis

Abstract: Introduction:This systematic review protocol describes the methods that will be used to evaluate the efficacy and safety of acupotomy for the treatment of lumbar spinal stenosis.Methods and analysis:The following electronic databases will be searched until December 2018 without language or publication status restrictions: five English databases, that is Medline, the Cochrane Central Register of Controlled Trials (CENTRAL), EMBASE, Allied and Complementary Medicine Database (AMED), and Cumulative Index to Nursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Therefore, there has recently been a growing interest regarding safer and more effective conservative treatments, such as acupuncture and acupotomy, which have been widely used in clinical practice for the treatment of LSS. Recently, various studies have reported the efficacy and safety of acupuncture and acupotomy in LSS [19–21] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there has recently been a growing interest regarding safer and more effective conservative treatments, such as acupuncture and acupotomy, which have been widely used in clinical practice for the treatment of LSS. Recently, various studies have reported the efficacy and safety of acupuncture and acupotomy in LSS [19–21] …”
Section: Discussionmentioning
confidence: 99%
“…Although the methodological quality of the study is poor and the number of good-quality RCTs few, the superiority of acupotomy has been reported in a meta-analysis [21] . While studies on the efficacy of acupotomy are ongoing, there are limitations to the application of these clinical studies in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Some studies have shown that acupotomy therapy can release adhesions, alter the mechanical balance of the knee joint, improve lymphatic circulation, and reduce abnormal tissue pressures. [ 12 ] Acupotomy has been widely used clinically with a satisfactory efficacy. With the development of ultrasound technology, ultrasound-guided acupotomy has shown great value in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The lumbar vertebrae is a major target treatment region for acupotomy therapy. 12 , 13 , 14 , 15 , 16 , 17 From clinicians’ point of view, the TPs and FJs are direct treatment targets for facet joint pain, lumbar spinal stenosis, and the 3rd transverse process syndrome. Further, the TPs and FJs are utilized as landmark structures when other muscles, such as the quadratus lumborum, iliopsoas, and multifidi, are stimulated.…”
Section: Introductionmentioning
confidence: 99%